Hak-Hak Perempuan Dalam Al-Qur’an: Studi Analisis Qs. Al-Nahl: 97 Perspektif M. Quraish Shihab - Syukkur, Abdul; Zelviana, Zulfa Annajah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
The marginalization of women's rights and roles is often pinned on Islamic teachings that are sourced from the Qur'an, but is it true that the argument for the castration of women's rights is in the Qur'an? The purpose of this study is to find common threads of similarities and differences between men and women according to the Qur'an, so that later it can be emphasized which women's rights are. This research is based on library data related to the subject matter discussed. The data collection method is sourced from primary and secondary data using content analysis. The results of the study reveal that, according to Quraish Shihab based on surah al-Nahl verse 97, it shows that men and women are both creatures of God. There is no difference between the two, the only difference is faith and piety. And this verse also shows how women are also required to be involved in activities that are beneficial, both for themselves and their families, as well as for society and the nation and mankind as a whole.